2021
DOI: 10.1051/e3sconf/202130801011
|View full text |Cite
|
Sign up to set email alerts
|

Water Supply: RO Desalination Versus Conventional Water Treatment

Abstract: Water scarcity threatens the health and development of countries worldwide due to the rapid expansion of population and climate change, pushing the government to find more innovative and sustainable ways to address water stress. Governments have adopted reverse Osmosis (RO) seawater desalination technology for its cheap raw water intake and stability. However, its environmental and financial sustainability remains disputable. In this study, three metrics, carbon footprint, cost, and waste discharge, are define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…With regard to company vehicles, there are, in general, vehicles associated with one or more installations, mainly for maintenance and overhaul work. Also, a study conducted in a desalination plant in California concluded that there was no CO 2 production from the facilities operation used in water transportation (Han et al 2021 ). Scope 2 Electricity consumption is the most important activity in the generation of emissions, due to the importance of the annual electricity consumption of installations such as wells and desalination plants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to company vehicles, there are, in general, vehicles associated with one or more installations, mainly for maintenance and overhaul work. Also, a study conducted in a desalination plant in California concluded that there was no CO 2 production from the facilities operation used in water transportation (Han et al 2021 ). Scope 2 Electricity consumption is the most important activity in the generation of emissions, due to the importance of the annual electricity consumption of installations such as wells and desalination plants.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to company vehicles, there are, in general, vehicles associated with one or more installations, mainly for maintenance and overhaul work. Also, a study conducted in a desalination plant in California concluded that there was no CO 2 production from the facilities operation used in water transportation (Han et al 2021 ).…”
Section: Resultsmentioning
confidence: 99%